THE INFLUENCE OF PERSONAL SELLING AND ADVERTISING ON CONSUMER BUYING DECISION AT VAPORZONE VAPESTORE MANADO - Joshua Christovel Pelle; David Paul Elia Saerang; Fitty Valdi Arie (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
This resarch aims to test the influence of Personal Selling and Advertising on Consumer Buying Decision at Vaporzone Vapestore Manado. The method that used in this study is multiple linear regression analysis, a sample was taken is 100 respondents. The results of this study shows tha Personal Selling has a significant effect on Consumer Buying Decision and Advertising has a significant effect on Consumer Buying Decision.